Water and post-conflict peacebuilding : soringup peace - Weinthal, Erika editor; Troell, Jessica editor; Nakayama, Mikiyasu editor (Abingdon, Oxon ; New York, NY : Earthscan, from Routledge, 2014)
Includes bibliographical references and index